Childhood Intestinal Parasitic Reinfection, Sanitation and Hygiene Practice in Eastern Ethiopia: Case Control Study - Gebru H; Deyessa N; Medhin G; Kloos H (Infection and Drug Resistance, 2024)
Heroda Gebru,1 Negussie Deyessa,2 Girmay Medhin,3 Helmut Kloos4 1Ethiopian Institute of Water Resources, Addis Ababa University, Addis Ababa, Ethiopia; 2School of Public Health, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 3Aklilu Lemma Institute of Pathobiology, Addis Ababa University, Addis Ababa, Ethiopia; 4Department of Epidemiology and Biostatistics, University of California, San Francisco, CA, USACorrespondence: Heroda Gebru, Email herodagebru13@gail.comBackground: The recurrence of intestinal parasitic infections (IPIs) can lead to different problems that can be transferred from generation to generation. Sanitation and hygienic practices have vital role in the parasitic reinfection. In poor hygienic and sanitation condition children may live in a continuous cycle of infection and reinfection.Objective: To assess childhood IP reinfection and its association with sanitation and hygienic practice in eastern Ethiopia.Methods: A population-based case-control design was used in this study. Data were collected from 75 reinfected cases and 147 unmatched controls. Fecal specimens were observed for parasites using direct smear and formol ether techniques. Epi-Info and SPSS (the statistical package for social science) were used for data entry and analysis, respectively. Logistic regression analysis was conducted to identify significant associations (P< 0.05) between variables.Results: The overall IP reinfection rate within 24 weeks after treatment was 33.8% (75/222), with a 95% CI=27.7%– 40.5%. The frequency of intestinal protozoa was 18%, and for helminths was 15.8%. Children who swam in a polluted water had 3.7 times greater odds of IP reinfection than children who did not swim (P =0 .01, 95% CI: 1.4– 10.0). Children who regularly bathed in streams and children who bathed both at home and in streams were found to have 12.6 times and 5.8 times higher odds of IP reinfection than children who bathed regularly at home (P=0.002, 95% CI:2.5– 64.8) and (P = 0.042, 95% CI:1.1– 31.3), respectively. Children in households that owned domestic animals had 4.5 times higher odds of IP reinfection than the reference group (P = 0.013, 95% CI: 1.3– 12.5).Conclusion: IP reinfection rates were significantly associated with habits of swimming in a polluted water, places of bathing, and ownership of domestic animals. Therefore, efforts should be made considering such factors to minimize IP reinfection in the area.Keywords: Ethiopia, hygiene, reinfection, sanitation